Effective Range of Percutaneous Posterior Full-Endoscopic Paramedian Cervical Disc Herniation Discectomy and Indications for Patient Selection. (26th October 2017) - Wen, Hongquan; Wang, Xin; Liao, Wenbo; Kong, Weijun; Qin, Jianpu; Chen, Xing; Lv, Hai; Friis, Thor
Abstract : The objective was to investigate the effective and safe range of paramedian CDH by percutaneous posterior full-endoscopy cervical intervertebral disc nucleus pulposus resection (PPFECD) to provide a reference for indications and patient selection. Sixteen patients with CDH satisfied the inclusion criteria. Before surgery the patients underwent cervical spine MRI, and the distance between the dural sac and herniated disc was measured. An assessment was performed by MRI immediately after surgery, measuring the distance between dural sac and medial border of discectomy (DSMD). The preoperative average distance between the dural sac and peak of the herniated disc (DSPHD) was 3.87 ± 1.32 mm; preoperative average distance between dural sac and medial border of herniated disc (DSMHD) was 6.91 ± 1.21 mm and an average distance of postoperative DSMD was 5.41 ± 1.40 mm. Postoperative VAS of neck and shoulder pain was significantly decreased but JOA was significantly increased in each time point compared with preoperative ones. In summary, the effective range of PPFECD to treat paramedian CDH was 5.41 ± 1.40 mm, indicating that DSMHD and DSPHD were within 6.91 ± 1.21 mm and 3.87 ± 1.32 mm, respectively. PPFECD surgery is, therefore, a safe and effective treatment option for patients with partial paramedian cervical disc herniation.